2005
DOI: 10.1007/s00204-005-0030-8
|View full text |Cite
|
Sign up to set email alerts
|

Subacute oral toxicity study of di(2-ethylhexyl)adipate based on the draft protocol for the “Enhanced OECD Test Guideline no. 407”

Abstract: We performed a 28-day repeated-dose toxicity study of di(2-ethylhexyl)adipate (DEHA) based on the draft protocol of the "Enhanced OECD Test Guideline 407" to investigate whether it has endocrine-mediated properties according to this assay. DEHA was orally administered to SD rats at doses of 0, 40, 200 and 1,000 mg/kg/day for at least 28 days, and disturbance of the estrous cycle and increased ovarian follicle atresia were detected in the 1,000 mg/kg group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…DEHA (1,000 and 2,000 mg/kg/day), a phthalate alternative, increased atresia in preantral and antral follicles (Miyata et al 2006; Wato et al 2009). ATBC (5 and 10 mg/kg/day), a phthalate alternative, decreased the numbers of primordial, primary, and secondary follicles, but did not alter the numbers of corpora lutea or atretic follicles in mouse ovaries (Rasmussen et al 2016).…”
Section: Plasticizer Alternativesmentioning
confidence: 99%
“…DEHA (1,000 and 2,000 mg/kg/day), a phthalate alternative, increased atresia in preantral and antral follicles (Miyata et al 2006; Wato et al 2009). ATBC (5 and 10 mg/kg/day), a phthalate alternative, decreased the numbers of primordial, primary, and secondary follicles, but did not alter the numbers of corpora lutea or atretic follicles in mouse ovaries (Rasmussen et al 2016).…”
Section: Plasticizer Alternativesmentioning
confidence: 99%
“…It has been reported that repeated dosing of peroxisome proliferators including DEHA induced hypertrophic changes of the liver and kidney, which was characterized by increases in the number of peroxisomes (Holden et al, 1999). Eosinophilic change of proximal tubule was observed in previous repeated dose toxicity studies of DEHA (Miyata et al, 2006) and DEHP (David et al -ered attributable to the PPAR activation.…”
Section: Sp106mentioning
confidence: 95%
“…DEHA is widely used as a plasticizer in extensive array products, and has been reported that disturbance of the estrous cycle and increased ovarian follicle atresia were observed in the 1,000 mg/kg group (Miyata et al, 2006). DEHA was orally administered to Crl:CD(SD) female rats at the doses of 0, 200, 1,000 and 2,000 mg/kg for 2 weeks Day 7 of gestation 21 ± 3 22 ± 2 22 ± 3 24 ± 3* Mean estrous cycle length (day) 4.6 ± 1.7 4.2 ± 0.3 4.8 ± 0.5* 5.4 ± 1.1** No.…”
Section: Sp106mentioning
confidence: 99%
See 1 more Smart Citation
“…There are no adequate performed studies, which allow a precise determination of a NOAEL for DEHA from subchronic or chronic studies. A recent study based on the draft protocol for the "Enhanced OECD Test guideline no 407" using oral administration of 0, 40, 200, and 1000 mg/day for 28 days showed a reduction in relative kidney weights at 200 and 1000 mg/kg/day (Miyata et al 2006).…”
Section: Toxicitymentioning
confidence: 99%